Separability Filter for Localizing Abnormal Pupil: Identification of Input Image - Retno Supriyanti; Elvin Pranata; Yogi Ramadhani; Tutik Ida Rosanti (Universitas Ahmad Dahlan, 2013)
Separability filter method is a reliable method for pupil detection. However, so far this method is implemented for detecting pupil of normal eye, while for abnormal eye such as cataract and glaucoma patients; they have different characteristics of pupil such as color, shape and radius size of pupil. In this paper we propose to use separability filter for detecting pupil of abnormal patients with different characteristics. We faced a problem about radius size, shape and color of pupil; therefore we implemented Hough Transform, Blob area and Brightness for identifying input images before applying separability filter. The experiment results show that we can increase performance of pupil detection for abnormal eye to be 95.65%.